American College Students Studying Abroad in China: Language, Identity, and Self‐Presentation. (21st May 2015) - Du, Hang
Abstract This article reports the results of qualitative analyses of data drawn from monthly informal individual interviews of 29 American college students who were spending one semester studying Mandarin Chinese abroad in a program in China. While some data confirm previous findings that some students' identification as Americans was strengthened during study abroad, data also indicate that students in this study took great pride in their Chinese proficiency, fully embraced their "foreigner identity, " and used it to their advantage. Studying in China did not seem to pose serious threats to this group of students' identity negotiation and self‐presentation. This research supports the call to conduct research regarding learners from a wider range of language backgrounds studying in a broader range of study abroad contexts so as to more fully understand the complexity of study abroad.